O tabu e o visível: tribalismo e política na eleição de 2019-2020 em Guiné-Bissau - Silva, Domingas da (2022)
This dissertation aims to analyze the practice of tribalism in Guinea-Bissau. It is an ethnography that explores the various aspects of tribalism that marked Guinean daily life as well as politics. Through Guinean social and ethnic relations, the taboo of tribalism and its visibilities and consequences in electoral periods are explored. In general, it explores some events that marked the 2019-2020 election such as hatred, violence, division, accusations between militants and politicians. Thus, it explores the discourse of living school versus school ika nada and viva Portuguese language versus living Creole language. And, finally, it analyzes the uses of ethnic-religious visual symbols by candidates as an easy phenomenon to be recognized on ballot papers by the electorate, drawing attention to their ethnic and religious group.